The Social Context of Mawlid Shifā’u al-Ṣudūr by Hadratus Syekh Arifin bin Ali bin Hasan - Argha Zidan Arzaqi; Masudin Nawawi (International Journal of Science and Environment (IJSE), 2025)
This study provides a sociological analysis of the authorship of Mawlid Shifā’u al-Ṣudūr by Hadratus Syekh Arifin bin Ali bin Hasan, a local scholar without formal literary training. The research aims to explore how his social status, ideology, and target community influenced the creation of this significant work. Using a qualitative approach with a descriptive-analytical design, the study examines the Mawlid Shifā’u al-Ṣudūr as its sample from the population of all Indonesian kitab mawlid. The researcher, acting as the main instrument, employed content and document analysis to systematically link the author's biographical and social context with the text's content. The findings indicate that the work is a product of a unique interplay between the author's ascribed, achieved, and assigned statuses, his mystical spiritual journey, and his adherence to the Nūr Muhammad concept. The study concludes that the book served as a tool for da'wah and identity formation, with its bilingual format specifically tailored for a community with low Arabic literacy. The findings are limited to this case, and further comparative research is suggested.